Protein Profile And Antigenicity Of Representative Leptospiral Serovars Reported In Malaysia And Experimental Leptospira Interrogans Infection In Dogs - Cheng, Kim Sing (2007)

(untitled)
Wide distribution of leptospires in the world has caused tremendous economic losses in agricultural sector due to decrease in animal production, quality of animal products and increased cost of treatments and also one of the public health concerns as this zoonosis has caused fatalities in human beings. In the study, immunoprobing experiments with rabbit antisera against serovars canicola, icterohaemorrhagiae, hardjobovis, pomona and australis, band with molecular weight 137.6 kDa is unique in serovar canicola 35 kDa in icterohaemorrhagiae, 10.5 kDa and 71.4 kDa in hardjobovis, 48.1 kDa in pomona while 20.9 kDa and 25.0kDa in australis. These distinct bands could have explained the selectiveness of different serovars on the target hosts, organs or perhaps tissues. In the experiment, Leptospira interrogans serovar canicola caused interstitial nephritis while serovar icterohaemorrhagiae caused liver damage in local stray dogs. Two dimensional SDS-Polyacrylamide Gel Electrophoresis (SDS-PAGE) on both serovars canicola and icterohaemorrhagiae have revealed differences in the protein distributions. Three different protein spots sharing the same molecular weights at 42.1kDa, 126kDa and 136 kDa while at 60.9kDa, 65.2kDa and 89.6kDa, two proteins spots sharing the same molecular weight were detected in serovar canicola. Serovar icterohaemorrhagiae on the other hand has three protein spots at 31kDa, 36kDa and 45kDa while 5 protein spots at 32 kDa were detected. Antibody titres peaked between 6 to 11 post inoculation day (P.I.D) with the highest titre at 1:1,600 in dogs infected with Leptospira canicola through intravenous route (Group 1). While dogs infected with serovar icterohaemorrhagiae through intravenous route had peak antibody titre between 9 to 11 (Group 2) P.I.D, with the highest titre at 1:1,600. Dogs infected with serovar icterohaemorrhagiae through oculonasal route (Group 3), the peak titre of antibody production was much delayed, at between 19 to 23 P.I.D but with much higher than the two previous tests (Group 1 and Group 2) at the highest titre reached was 1:3,200. The study also shows that dogs once infected with leptospiral serovar, especially through oculonasal route, would shed the organism in its urine for a long period of time up till the end of study (nine months). This reflects the oculonasal route to be the actual route which dogs are most likely to be infected by leptospires in natural environment.